Study on properties of permeable brick. Issue 1 (August 2021) - Zhixuan, Zhang; Bin, Yang; Na, Zhu; Ying, Lin; Bo, Ma; Meijie, Wang; Yujuan, Liu
Abstract: The performance research and preparation methods of different kinds of permeable brick are analyzed and summarized, which shows the wide application prospect of permeable brick.